Sinonasal Cancer Cases in a Nationwide Hospital Cancer Registry in Brazil, 2007-2021 - Koller, Francisco; Consonni, Dario; Mensi, Carolina; Nogueira, Luciana de Alcantara; Ribeiro, Cristiano de Oliveira; Guimarães, Paulo Ricardo Bittencourt; Kalinke, Luciana Puchalski (La Medicina del Lavoro, 2024)
Background: Sinonasal cancers (SNC) are rare cancers with a high proportion attributable to occupational carcinogens. This study aims to describe the sociodemographic, clinical, and occupational characteristics of subjects with SNC in Brazil. Methods: Observational study conducted with secondary data from a network of Hospital Cancer Registries. We selected epithelial/unspecified SNC records with a year of diagnosis from 2007 to 2021. We performed descriptive statistics of SNC cases and calculated crude and age-standardized rates (ASR, standard: world population) by gender and Region of residence. Results: We identified 2,384 cases, 1,553 (65.1%) in men and 831 (34.9%) in women. The mean age at diagnosis was 59 years for both. Most SNC (50.7% in men and 53.2% in women) originated from the maxillary sinus. Most (65.5% in men and 54.5% in women) were squamous cell carcinomas. Information on occupation was missing in the years 2019-2021. Most male SNC patients (44.8%) were employed in group 6 (Agricultural, forestry, and fishing workers), while women had been mainly (34.6%) working in groups 8 (Workers in the production of industrial goods and services, machine operators) and in group 6 (27.6%). Crude SNC incidence rates were 1.0 per million person-years in men and 0.5 in women, while ASR were 1.0 and 0.4, respectively. In both genders, the highest ASR was in Minas Gerais (men: 1.9; women: 0.7). Conclusions: Establishing the profile of Brazilians with sinonasal cancer can stimulate epidemiologic research for monitoring this group of cancers with a high association with occupational exposures.